Optimalisasi Pengaturan Jarak Tanam dan Pemberian Pupuk P Terhadap Produksi Tanaman Jagung Pulut (Zea mays ceratina kulesh) - Firoh, Faridatul Maag; Jumiatun, Jumiatun; Utami, Christa Dyah (Agropross : National Conference Proceedings of Agriculture, 2023)
Pulut corn is a type of corn that has a fluffier taste and has the advantage of being able to keep blood sugar levels stable. The need for corn commodity continues to increase along with the increase in population. The purpose of this study was to determine the effect of spacing and application of P fertilizer on growth and production of corn pulut. This research was conducted in September 2022-November 2022 in Antirogo Village, Sumbersari District, Jember Regency. The research design used was a factorial randomized block design (RBD). The first factor is the spacing consisting of conventional spacing of 70cm x 20 cm and row spacing of 2:1 legowo with a spacing of 40cm x 20 cm x 100 cm. The second factor is the application of P fertilizer with 5 levels, respectively 100kg/ha, 125kg/ha, 150kg/ha, 175kg/ha, and 200kg/ha. There was an interaction between the treatment of jajar legowo spacing and 200 kg/ha P fertilizer on stem diameter. Treatment Jajar legowo spacing has a significantly different effect on the observation of cob diameter and light intercept. Meanwhile, the P fertilizer treatment had a significantly different effect on cob weight. Based on these results, it can be concluded that the use of a spacing of 70 x 20 cm can increase cob diameter and P fertilization at a dose of 100 kg/ha can increase cob weight.